How Informed Citizens, Prospective Teachers Are? An Exploratory Study of Political Interest and Political Efficacy - Gardia, Alok; Singh, Somu (JOURNAL OF INDIAN EDUCATION, 2009)
An informed and competent citizenry is the basic essential for the progress and prosperity of any country in the world. A country is known by its citizens; their skills, resourcefulness and most importantly their participation into political issues contributes towards national progress. But nowadays, the bond of democracy is weakening which is an alarming concern; particularly for education which is the strongest agency to provide effective membership for the society. Therefore, we need teachers as informed citizens who can work as role models. In this premise, an empirical study was conducted to study the political interest and efficacy of prospective teachers. The results indicate that prospective teachers are better in political interest than political efficacy. Various personal and environmental variables of the study showed different pattern of influence in which the prominence of family is reaffirmed. On the whole, the study recommends including education of democratic citizenship in teacher education programs and outlines the importance of teachers in education of democratic citizenship.